MICROSTRUCTURAL AND TRIBOLOGICAL PROPERTIES OF NICKEL-BASED HARDFACING COATINGS APPLIED ON NITRIDING STEELS BY PLASMA TRANSFERRED ARC WELDING - Abdullah Sert; Fatih Hayati Çakır; Gökçe Mehmet Ay (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi)
Plasma Transferred Arc (PTA) coatings are widely used for the surface modification of metals due to their ability to achieve high coating thickness, low thermal stress, and high energy density. This technique is commonly applied to glass and ceramic molds, automotive valves, petrochemical vanes, lamination cylinders, as well as plastic extrusion molds and screws. In plastic injection machine screws, high hardness and wear resistance are essential for durability. To achieve these properties, the steels used in plastic injection screws are first hardfaced on the thread crests using the PTA coating method and then nitrided. In this study, 1.8550 and 1.8519 steels, commonly used in plastic injection screw manufacturing, were coated with two different powders: FeCrBSi with a nickel (Ni) balance, either with or without tungsten (W) addition. The tribological properties of the coated samples were evaluated through ball-on-disc wear tests. The samples were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and optical microscopy. The depth and width of wear tracks were measured using a profilometer. Results indicated that increasing W content leads to a higher coefficient of friction, but the best wear performance was observed with W-containing coatings. The optimal combination was found to be the 1.8550 steel substrate paired with the FeCrBSi-W coating, which demonstrated a 5% higher coefficient of friction but a 47% lower specific wear rate compared to the non-W coating.